Phase aberration simulation study of MRgFUS breast treatments. Issue 3 (23rd February 2016) - Farrer, Alexis I.; Almquist, Scott; Dillon, Christopher R.; Neumayer, Leigh A.; Parker, Dennis L.; Christensen, Douglas A.; Payne, Allison
Abstract : Purpose: This simulation study evaluates the effects of phase aberration in breast MR‐guided focused ultrasound (MRgFUS) ablation treatments performed with a phased‐array transducer positioned laterally to the breast. A quantification of these effects in terms of thermal dose delivery and the potential benefits of phase correction is demonstrated in four heterogeneous breast numerical models. Methods: To evaluate the effects of varying breast tissue properties on the quality of the focus, four female volunteers with confirmed benign fibroadenomas were imaged using 3T MRI. These images were segmented into numerical models with six tissue types, with each tissue type assigned standard acoustic properties from the literature. Simulations for a single‐plane 16‐point raster‐scan treatment trajectory centered in a fibroadenoma in each modeled breast were performed for a breast‐specific MRgFUS system. At each of the 16 points, pressure patterns both with and without applying a phase correction technique were determined with the hybrid‐angular spectrum method. Corrected phase patterns were obtained using a simulation‐based phase aberration correction technique to adjust each element's transmit phase to obtain maximized constructive interference at the desired focus. Thermal simulations were performed for both the corrected and uncorrected pressure patterns using a finite‐difference implementation of the Pennes bioheat equation. The effect of phase correction was evaluated through comparison of thermal dose accumulation both within and outside a defined treatment volume. Treatment results using corrected and uncorrected phase aberration simulations were compared by evaluating the power required to achieve a 20 °C temperature rise at the first treatment location. The extent of the volumes that received a minimum thermal dose of 240 CEM at 43 °C inside the intended treatment volume as well as the volume in the remaining breast tissues was also evaluated in the form of a dose volume ratio (DVR), a DVR percent change between corrected and uncorrected phases, and an additional metric that measured phase spread. Results: With phase aberration correction applied, there was an improvement in the focus for all breast anatomies as quantified by a reduction in power required (13%–102%) to reach 20 °C when compared to uncorrected simulations. Also, the DVR percent change increased by 5%–77% in seven out of eight cases, indicating an improvement to the treatment as measured by a reduction in thermal dose deposited to the nontreatment tissues. Breast compositions with a higher degree of heterogeneity along the ultrasound beam path showed greater reductions in thermal dose delivered outside of the treatment volume with correction applied than beam trajectories that propagated through more homogeneous breast compositions. An increasing linear trend was observed between the DVR percent change and the phase‐spread metric ( R 2 = 0.68). Conclusions: These results indicate that performing phase aberration correction for breast MRgFUS treatments is beneficial for the small‐aperture transducer (14.4 × 9.8 cm) evaluated in this work. While all breast anatomies could benefit from phase aberration correction, greater benefits are observed in more heterogeneous anatomies.